Microbial contamination of dental radiology equipment - Hussin, Akbar Sham; Ramli, Mohd Fauzan; Yusoff, Azizah (Japan International Cultural Exchange Foundation, 2009)
Objective: The aim of this study was to determine the quantity of colony forming units of microbial contamination present on the high touch areas of dental radiology equipment. Methodology: Swabs were taken from 4 high touch areas of the dental radiology equipment on 6 days. The swabs were sent to the laboratory in the transport medium(Broth Medium)and incubated for 48 hours at 37 °C, before being smeared on the nutrient and blood agar media for isolation of microorganisms for 72 hours at 37 °C. Quantification of Colony Forming Units (CFU) was undertaken to determine the quantity of microbial contamination. Results: All the high touch areas on the dental radiology equipment showed high CFU counts. The median (IQR) values between the 4 high touch areas of equipment were not significantly different for both the nutrient and blood agars. (NA P = 0.168, BA P = 0.270). Surface disinfection produced decreased microbial contamination. Conclusion: The results demonstrated the presence of high levels of bacterial contamination of the high touch areas of dental radiology equipment without proper disinfection.